2017
DOI: 10.1097/aap.0000000000000639
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Regional Anesthesia Simulation Training

Abstract: Ultrasound-guided regional anesthesia knowledge and skills significantly improved with simulation training. The acquired UGRA skills may be transferred to the clinical setting; however, further studies are required to confirm these changes translate to improved patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 24 publications
0
54
0
2
Order By: Relevance
“…Simulation training may hold the key to achieving this formidable task 64. Image guidance continues to be widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation training may hold the key to achieving this formidable task 64. Image guidance continues to be widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Practice for regional anesthesia via simulation training may improve needle handling and facilitate the localization of targets [6][7][8]. Simulation training can entail virtual reality, bench model simulators, human cadavers, and animal carcasses [8].…”
Section: Introductionmentioning
confidence: 99%
“…A need exists to develop accurate and reliable metrics that quantify translation of regional anaesthesia skills. A recent systematic review demonstrated large heterogeneity for type of participants, mode of simulation, and outcome 1 . Metrics include task and error checklists, eye gaze tracking, and global rating scores.…”
mentioning
confidence: 99%
“…The presence of trans-laryngeal or tracheostomy tubes impairs communication, leading to frustration and anxiety for patients and staff, and dissatisfaction with care. 1 Augmentative and alternative communication (AAC) includes a range of strategies and devices intended to facilitate communication. 2 With technology developing rapidly we conducted a literature review of AAC strategies to inform our research in this field.…”
mentioning
confidence: 99%